1992
DOI: 10.1093/infdis/166.3.646
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Chlamydia pneumoniae TWAR Infection in Seattle Families, 1966-1979

Abstract: Incidence rates of Chlamydia pneumoniae infection and information on reinfection and transmission within families were obtained by serologic study of serum samples from prospective family studies conducted 1966-1979. Specimens (n = 3671) from 343 subjects in 68 families were tested for TWAR antibody using the microimmunofluorescence assay. Acute infection was defined as a fourfold rise in antibody titer between consecutive specimens. Sixty-four episodes of infection were identified in 58 persons; 4 had 2 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
1
6

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 9 publications
9
86
1
6
Order By: Relevance
“…We entirely agree that it is unlikely that a 22% cumulative incidence rate over 3 months was caused by acute exogenous infections because, as D.L. Hahn states, the annual nonepidemic C. pneumoniae acute infection rate in the adult population is reported to be ,2% [8]. To our knowledge, our study was not conducted during a community epidemic of C. pneumoniae infection [1].…”
Section: From the Authorssupporting
confidence: 50%
“…We entirely agree that it is unlikely that a 22% cumulative incidence rate over 3 months was caused by acute exogenous infections because, as D.L. Hahn states, the annual nonepidemic C. pneumoniae acute infection rate in the adult population is reported to be ,2% [8]. To our knowledge, our study was not conducted during a community epidemic of C. pneumoniae infection [1].…”
Section: From the Authorssupporting
confidence: 50%
“…11 Antibody prevalence studies suggest that Ͼ50% of adults have been exposed to it. 12 C pneumoniae, an obligate intracellular parasite, is known to readily infect mononuclear phagocytes. 8 Macrophages, which derive from monocytes, are characteristically localized within atherosclerotic plaques.…”
Section: See P 1538mentioning
confidence: 99%
“…Seroepidemiological studies performed worldwide have demonstrated that 40%-86% of asymptomatic adults have antibodies to C. pneumoniae [6][7][8][9]. In Jordan, a single study demonstrated 61.1% seroprevalence of C. pneumoniae-specific IgG antibodies among apparently healthy male adults [10].…”
Section: Introductionmentioning
confidence: 99%